Dislocation of the Temporomandibular Joint A Guide to Diagnosis and Management (Springer International Publishing, 2018)
This book provides a comprehensive overview of dislocation of the temporomandibular joint (TMJ), covering all relevant aspects, from aetiology and diagnosis to management. The treatment-oriented chapters describe nonsurgical, surgical and arthroscopic interventions, and the book closes by examining the role of total alloplastic reconstruction of the TMJ in patients with chronic jaw joint dislocation. Each chapter commences with a summary of key points and the clearly written text is supported by numerous clinical photographs, as well as by videos to which the reader will have online access. All of the authors are recognized experts in the topics that they discuss. Dislocation of the TMJ constitutes a medical emergency since prompt treatment is required in order to prevent the harmful sequelae that may arise once spasm of the muscles of mastication has become established, preventing return of the condyle into the glenoid fossa. If the condition is left untreated, radica l corrective surgery may be required to restore jaw function and eliminate pain. In presenting state of the art knowledge on TMJ dislocation, this book will be of value for all involved in the management of the condition.